HUBUNGAN STATUS GIZI DENGAN KADAR HEMOGLOBIN PADA REMAJA PUTRI DI SMK KARTIKA IV-1 MALANG - Zangga, Mardiana Ina; Maulina, Rifzul; Sulistiyah, Sulistiyah (NHM PRESS, 2024)
Indonesia is a country that faces many nutritional problems which have a serious impact on the quality of human resources (HR). One of the problems of malnutrition that is still quite high in Indonesia is anemia in women of childbearing age (WUS). The prevalence of anemia according to the World Health Organization (WHO) collected from 1993 to 2005 is estimated at around 1.6 billion people, 1/4 of the world's population suffers from anemia. Meanwhile, the anemia rate in the WUS group was 57%. In East Java Province the anemia rate is 9.6%. This figure is still lower than the national incidence rate of 28%. The type of research used in this research is Correlation Analysis, which is a research method that involves collecting data to determine whether there is a relationship and the level of relationship between two or more variables using a cross sectional approach where the researcher will carry out observations or measurements of variables at the same time. The population of 11th grade teenage girls at SMK Kartika IV-1 Malang is 60 people. The sample technique uses simple random sampling. The number of samples in this research was 38 respondents. The research results showed that the majority of respondents had a nutritional status in the good category, almost half of the respondents had a nutritional status in the sufficient category, and a small number of respondents had a nutritional status in the poor category. Most of the respondents had hemoglobin levels in the normal category, almost half of the respondents had hemoglobin levels in the high category, and a small number of respondents had hemoglobin levels in the low category. There is a relationship between nutritional status and hemoglobin levels in young women at Vocational School Kartika IV-1 Malang, with the results of the chi square test showing Pvalue = (0.000) < (0.05).